Machine Man - Moral, Alfonso; Corella, Roser (Moral, Alfonso ; Corella, Roser, 2011)
Verzio9 FF Submission. Duration: 00:15:00 In Bangladesh thousands of people perform machine-like repetitive manual work. Barefoot women collect coal. Boys produce 18,000 bricks a day. A man weighing fifty kilos moves hundred-kilo sacks. Children sort plastic bottles for twelve hours each day. Men dismantle rusty wrecks in a polluted river. When they speak of the work that destroys their health, which in Europe would be considered inhumane, many say: "I feel like a machine." Despite the proliferation of modern machinery, this film captures people still performing back-breaking and dangerous work by hand.